Factors influencing brands’ reputation on social media - Alves Joana; Teixeira Sara; Oliveira Zaila; Teixeira Sandrina (Management şi Marketing)
Social networks considerably impact brand reputation, influencing consumer behaviour, perceptions, and purchase intentions. The content of brands on social media is central to consumer attitudes and behaviour and the formulation of opinions about the brand and its reputation. Therefore, this research aims to identify the factors that influence the reputation of brands on social media. A quantitative methodology was adopted using the online questionnaire data collection technique through a non-probabilistic convenience sample (N=185). After statistical analysis using PLS-SEM, the results show that social media influencers contribute to brand reputation on social networks. This article contributes to understanding the role of social networks in brand reputation by showing the aspects that most influence reputation and providing marketing professionals and managers with the most effective tools for their brands’ reputation.